ANALISIS ASUHAN KEPERAWATAN PADA PASIEN DENGAN RISIKO BUNUH DIRI AKIBAT DEPRESI DENGAN INTERVENSI GUIDED IMAGERY DAN FOCUS GROUP DISCUSSION DI RUANG JIWA INTENSIF CAMAR RS JIWA PROVINSI JAWA BARATTAHUN 2026 - Ai Mona; Tonika Tohri; Budi Rustandi (SINERGI : Jurnal Riset Ilmiah, 2026)
Background: Depression is a mood disorder that significantly increases the risk of suicide, particularly among patients in acute psychiatric intensive care settings. Suicide risk management is a priority in nursing care as it directly relates to patient safety. Non-pharmacological interventions such as Guided Imagery and Focus Group Discussion (FGD) may help stabilize emotions and improve coping mechanisms. Objective: To analyze nursing care for patients at risk of suicide due to depression through the implementation of Guided Imagery and Focus Group Discussion interventions in a psychiatric intensive care unit. Methods: This study employed a descriptive analytic method with a case study approach. Data were collected through observation, interviews, active participation, documentation review, and literature study. The subject was a patient diagnosed with depression and high suicide risk admitted to a psychiatric intensive care unit. Interventions were implemented in stages, beginning with Guided Imagery for emotional stabilization, followed by FGD to enhance social support and coping skills. Evaluation was conducted by assessing behavioral changes, emotional responses, and suicide risk scores. Results: The findings showed a significant reduction in suicide risk scores from high risk (scores of 14 and 11) to low risk (score of 3) after the interventions. Patients reported feeling calmer, more comfortable, experiencing fewer negative thoughts, and showing increased motivation to live. FGD facilitated emotional expression and strengthened social support. Conclusion: The implementation of Guided Imagery and Focus Group Discussion was effective in reducing suicide risk among patients with depression in a psychiatric intensive care setting. These interventions can be integrated into comprehensive nursing care to support suicide prevention efforts